MEDIA ANIMASI INTERAKTIF BERBASIS PBL BERMUATAN CERITA RAKYAT BIMA UNTUK MENINGKATKAN KARAKTER DAN LITERASI DIGITAL SISWA SMP - Jumrah Jumrah; I Gde Wawan Sudatha; I Made Tegeh (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
This study aims to develop interactive animation media based on Problem-Based Learning (PBL) integrated with Bima folklore "La Bibano Putri Kalepe" to improve the character and digital literacy of seventh-grade students at MTsN 5 Bima. The low character values and weak digital literacy skills among junior high school students served as the primary background of this study. The Research and Development (R&D) method was employed using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of 30 seventh-grade students selected through purposive sampling. Data were collected through expert validation questionnaires, character observation sheets, and pretest-posttest instruments. Validation results showed very valid percentages: media expert 92%, instructional design expert 90%, content expert 94%, and instrument expert 91%. Student responses regarding media practicality reached 91.67% (very practical). Gain score analysis showed an improvement in mean learning outcomes from 62.00 (pretest) to 87.00 (posttest) with an N-Gain of 0.66 (moderate-high category). Student character aspects improved significantly: responsibility 90%, social awareness 88%, leadership 89%, and digital ethics 91%. It is concluded that the developed media is proven valid, practical, and effective in improving character and digital literacy of junior high school students.